The Terrorism of ‘Counterterrorism’: The Use and Abuse of Anti-Terrorism Law, The Case of Ethiopia - Kibret, Zelalem (European Scientific Journal, ESJ, 2017)
Since its enactment on July 2009, Ethiopia’s anti-terrorism proclamation was/is at the very center of almost every political discourse in the nation. Many dissidents fall into its trap and by day its effect is becoming more far-reaching and resonating. The widely written provisions of the law make it susceptible to misapplication and prone to abuse. Whilst the state is staunchly firing back to the detractors of the law and its mis(application), however, it doubled down its implementation by every new day. This paper, after examining one hundred twenty three terrorism charges against nearly one thousand individuals―in a sixty-six months period of time―concludes that: Ethiopia’s anti-terrorism law is a colossal failure for counterterrorism, which only exemplifies how not to counter terrorism.